AN EVALUATION OF THE IMPACT OF CAPITAL STRUCTURE ON FIRMS' PERFORMANCE : A QUANTITATIVE STUDY OF SELECTED NON-FINANCIAL FIRMS LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE PERIOD 2005-2012 - Argeta, Argeta; Putri, Niken S. (Emerging Markets : Business and Management Studies Journal, 2013)
Capital structure is an important element for every company and directly affects the firms' performance and financial position. This study aims to evaluate the impact of capital structure on the performance of non-financial firms listed on the Indonesia Stock Exchange during the period 2005-2012. The data consist of 150 publicly listed non-financial firms from 8 non-financial industries in Indonesia. Panel data for the selected firms were generated and analyzed using both fixed effect model and random effect. The result shows that capital structure (DAR) has a significant impact on firms' performance (ROA, ROE, and GPM) and has no significant impact of capital structure on firms' performance caused by industry differences. Infrastructure, utilities, and transportation industry has the strongest industry effect on the impact of capital structure on firms' performance.